Networked multi pipeline pressure synchronous coordinated predictive control based on the model free adaptive method. (15th August 2019) - Wu, You; Liu, Guo-Ping
In order to achieve the rapid and accurate synchronous coordination of multi pipeline pressure systems using networked control system theory, an adjacent cross-coupling structure is adopted to improve the synchronisation performance. Considering the possible limitations of network communication, a networked predictive control algorithm based on model free adaptive control is proposed to compensate the delay caused by network. The above two strategies are combined to form the networked multi pipeline pressure synchronous coordination predictive control systems. The simulation experiments of synchronous coordinated control of three pipeline pressure systems are carried out on Simulink platform. The simulation results show that the proposed control scheme can compensate the network delay, and improve the dynamic and synchronous performance. The effectiveness of the control scheme is verified.